Agro-industrial residues as a source of volatile fatty acids: state of the art and innovative enhancers (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
The synthesis of volatile fatty acids (VFAs) from agro-industrial residues represents a sustainable strategy for producing higher value-added products compared to traditional methods. This work aims to highlight recent scientific advancements in VFA synthesis utilizing low-cost technologies. A comprehensive bibliographic analysis was conducted to identify the operational, physicochemical, and biological parameters influencing VFA generation from both inoculum sources and the biomass scheduled for valorization. The reviewed literature emphasized the application of biochar as a catalytic and stabilizing agent during the hydrolysis and acidogenesis processes. Additionally, the use of ruminal fluid as a microbial consortium, enriched with hydrolytic enzymes capable of degrading polysaccharides, was noted. The findings suggest that the combined application of these components has significant potential to enhance both the profitability and productivity of VFA production, thereby contributing to the advancement of a diversified circular economy.